2014
DOI: 10.1103/physrevb.89.115313
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin GaN nanowires: Electronic, thermal, and thermoelectric properties

Abstract: We present a comprehensive computational study of the electronic, thermal, and thermoelectric (TE) properties of gallium nitride nanowires (NWs) over a wide range of thicknesses (3-9 nm), doping densities (10 18 -10 20 cm −3 ), and temperatures (300-1000 K). We calculate the low-field electron mobility based on ensemble Monte Carlo transport simulation coupled with a self-consistent solution of the Poisson and Schrödinger equations. We use the relaxation-time approximation and a Poisson-Schrodinger solver to c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 98 publications
0
23
0
Order By: Relevance
“…In polar semiconductors the electron-longitudinal optical (LO) phonon scattering is the dominant inter subband scattering mechanism for separations of the sub-bands less than the LO phonon energy [6]. Polar optical phonon (POP) energy for the wurtzite GaN crystal is higher (ħω op = 92meV) [1] than other III-V semiconductors.…”
Section: Optical Phonon Scatteringmentioning
confidence: 99%
“…In polar semiconductors the electron-longitudinal optical (LO) phonon scattering is the dominant inter subband scattering mechanism for separations of the sub-bands less than the LO phonon energy [6]. Polar optical phonon (POP) energy for the wurtzite GaN crystal is higher (ħω op = 92meV) [1] than other III-V semiconductors.…”
Section: Optical Phonon Scatteringmentioning
confidence: 99%
“…25 This deviation is due to POP scattering, which forbids electrons with energies smaller than ℏ OP from emitting optical phonons. 29 The slight difference in the calculated values of d for the thick and thin GaN sample is found to arise from the difference in the roughness scattering component of ( ). We observe that the Seebeck coefficient for the thin GaN sample agrees well with the calculated d , however this model cannot describe the thick GaN sample ( Figure 2d).…”
mentioning
confidence: 93%
“…Although NWs can have different cross sections, we consider for simplicity a square crosssectional morphology with the understanding that the wire thickness or width stands in for a generic characteristic crosssectional feature size [17]. In Section 2, expressions for piezoelectric momentum relaxation rates are obtained for both ZB and WZ phases.…”
Section: Introductionmentioning
confidence: 99%
“…Electron mobility, one of the important electronic properties determining the performance of many semiconductor devices, has been investigated in GaN as well as ZnO NW systems [2,4,16,17]. Goldberger et al [4] have reported an average value of m ¼0.137 0.05 Â 10 À 2 m 2 V À 1 s À 1 , in ZnO NWs of diameter 101 nm and relatively low carrier concentrations of 5.2 72.5 Â 10 23 m À 3 in the temperature range 25 oT o300 K. On the other hand, a range of values of the electron mobility in GaN NWs, grown by different growth methods and having different cross sections, diameters and carrier density, are reported [2,16].…”
Section: Introductionmentioning
confidence: 99%